A Critical Review on the Book The Theories of Organizational Behavior - Mohammad Mobini (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Organizational Behavioral Theories are a major part of organizational studies because behavioral reasoning is found in a wide range of theoretical approaches. Behavioral theory begins with the organization's classical theories and ends with the company's main behavioral theory and then with evolutionary theory, organizational ecology, institutional theory, and transaction cost theory. The purpose of the present article is to review the book “Behavioral Theories of the Organization” written by Seyed Ali Akbar Afjeh. The author has tried to adapt the theories of the individual, the group and the organization to the behavioral sciences in Islamic management, and to apply them. He has also added Japanese and scientific management styles. By compiling his collection of studies in the form of a volume, the author believes that this work is a useful guide in the field of theory of behavior and behavioral theories in the organization. The text of the book is relatively fluent. A look at the structure of this work shows that the author has compiled this book without observing a specific scientific methodology. A clear definition of the organization's behavioral theories is not provided, and the introduction of the "school" in this work as a "method" confuses the reader in understanding the author's intent. It seems that the author seeks to the Islamize foundations of management, which has not been successful in this regard either.